Metabolic adjustment of glycine max (L.) merril in the presence of nitrate and bradyrhizobium japonicum - Júnior, Alberto Mongolo [UNESP] (2021)
Reactive oxygen species are generated during the processes of photosynthesis and nitrate reduction, which can compromise the integrity of biomolecules and membranes. During the vegetative phase of Fabaceae species, around half of translocated carbohydrate is used for nodule growth, while the other half returns to the aerial part with nitrogen incorporated. These sugars may be yet involved with membrane stabilization, signaling, and activation of important genetic pathways for plant development. Thus, the aim was to study the adjustments of the photosynthetic and antioxidant systems and the accumulation of carbohydrates and biomass in Glycine–Bradyrhizobium cultivated with nitrate (NO−3 ). Four treatments were evaluated in completely randomized blocks. Glycine–Bradyrhizobium was grown with 1.7 mM of NO−3(GB: 1.7 mM NO−3) and without NO−3(GB: 0 mM NO−3), andGlycinewas grown with 1.7 mM of NO−3(G: 1.7 mM NO−3) and without NO−3 (G: 0 mM NO−3 ). Glycine–Bradyrhizobium symbiosis contributes to photosynthetic metabolism and total sugars, reduces the action of antioxidant enzymes, and minimizes the use of nitrate in soybean cultivation.; Glycine–Bradyrhizobium with nitrate provided greater plant dry mass in the vegetative phase, along with increased enzymatic activity and reduced nodule mass.